Vegetation indices monitoring by using copernicus data in the old-growth forests of the Republic of Srpska/Bosnia and Herzegovina - Govedar, Zoran; Anikić, Nemanja (Frontiers in Forests and Global Change, 2024)
There are three Old-Growth Forests in Republika Srpska/Bosnia and Herzegovina (Lom, Janj and Perucica). Old-growth forests are vital for global biodiversity, acting as irreplaceable carbon sinks, fostering ecosystem stability, and preserving unique ecological and cultural heritage. They are dominated by mixed forests of beech, fir and spruce (Piceo-Abieti-Fagetim illyricum).The Old-Growth Forests boast an array of tree species, showcasing richness and diversity in the forest canopy.. Parts of Old-Growth Forests are located in different stages of development and trees in them are characterized by different degrees of vitality and have different values of vegetation indices. It is assumed that parts of Old-Growth Forests in the terminal phase of development with a large number of diseased and rotting trees have the lowest sizes of vegetation indices. This research aims to characterize old-growth forests from space through vegetation indices, in order to obtain a more in-depth analysis of the ecological condition of these forests. The analysis included the Normalized Difference Vegetation Index (NDVI), improved vegetation index (EVI), Soil Adjusted Vegetation Index (SAVI) and Visible atmospheric resistance index (VARI). The analysis of satellite imagery and the derived sizes of vegetation indices indicate a notable disparity in the sizes of Old-Growth Forests. The Old-Growth Forests Janj, evi and savi Old-Growth Forests Perucica has the highest values of NDVI, and the Lom Old-Growth Forests has the highest value of the VARI index. The results of these studies show that there are statistically significant differences in the sizes of vegetation indices between rainforests. Given the relatively small number of sample areas included in these studies, it is necessary to carry out similar studies on a larger number of sample areas (repetitions), especially during the growing season.